RETRACTED: An empirical investigation of firm performance through corporate governance and information technology investment with mediating role of corporate social responsibility: Evidence from Saudi Arabia telecommunication sector - Alfalah, Adel Abdulmhsen; Muneer, Saqib; Hussain, Mazhar (Frontiers in Psychology, 2022)
This study intended to examine the effect of IT investment and corporate governance mechanism on the performance of the Saudi telecommunication sector with mediating role of corporate social responsibility. Survey method was used to collect data from targeted Saudi telecom firm. Results show that corporate governance practices i.e. internal audit, internal audit committee and internal board size has significant and positive relationship with firm performance. Furthermore, IT investment positively affects the performance of Saudi telecommunication firms. Moreover, corporate social responsibility mediates the relationship between internal audit, internal audit committee, internal board size, IT investment and firm performance. This study contributes to the body of knowledge regarding IT investment, corporate governance mechanism, corporate social responsibilities and firm performance of telecommunication firms in emerging markets. Furthermore, this study will help top management of telecom firms to improve corporate governance and IT investment which will be beneficial to enhance firm performance.